Alternative dispute resolution in family disputes in Europe and Chile: mediation - Carolina Riveros; Dagmar Coester-Waltjen (Revista Direito GV)
Abstract The purpose of this paper is to examine whether the issues in family mediation are similar in Europe and Chile. The use of mediation in the world represents a significant progress in protecting family agreements and their autonomy. We conclude that Europe and Chile have to pay special attention to the quality control mechanisms and training of the mediators in family disputes.